010 Neuroimaging and CSF findings in autoimmune encephalitis with neuronal cell surface antibodies. (29th July 2019) - Broadley, James; Wesselingh, Robb; Beech, Paul; Seneviratne, Udaya; Buzzard, Katherine; Butzkueven, Helmut; O'Brien, Terence; Monif, Mastura
Abstract : Introduction: Neuroimaging and CSF analysis compose essential steps in evaluating patients with autoimmune encephalitis (AE). No study has compared the magnitude and prognostic implications of these findings between different subtypes. Herein we examine cases of AE with neuronal cell surface antibodies, and contrast the results of early investigations. Methods: We performed medical records search from 2008–2018 in 5 Victorian hospitals. Cases of AE were established in accordance with diagnostic criteria by Graus et al. 1 Clinical and laboratory data was collected. All neuroimaging was evaluated independently by a neuroradiologist. Results: We identified 52 patients with AE with neuronal cell surface antibodies (21 NMDAR, 27 VGKC, 3 AMPAR, 1 GABAb). We found that among patients with anti-LGI1 antibodies the presence of abnormal CSF correlated with increased rates of mortality (50% vs 0%). This effect was largely mediated by CSF lymphocytosis, which was present in 2 patients who both died within 12 months of diagnosis. We found that the development of hippocampal atrophy was more common amongst patients with abnormal MRI findings, but in particular those with changes affecting the medial temporal lobe. This effect was evident both in the cases with anti-VGKC antibodies (60% vs 18%, 75% vs 17%) and the cohort as a whole (56% vs 15%, 83% vs 13%). Conclusions: This is the first study of its kind in Australia, and identifies some unique correlation between early investigation findings, and the clinical and radiological outcome. A larger cohort is required to determine if these findings are statistically significant. Reference: Graus F, Titulaer MJ, Balu R, Benseler S, Bien CG, Cellucci T, Cortese I, Dale RC, Gelfand JM, Geschwind M, Glaser CA, Honnorat J, Hoftberger R, Iizuka T, Irani SR, Lancaster E, Leypoldt F, Pruss H, Rae-Grant A, Reindl M, Rosenfeld MR, Rostasy K, Saiz A, Venkatesan A, Vincent A, Wandinger KP, Waters P, Dalmau J. A clinical approach to diagnosis of autoimmune encephalitis. Lancet Neurol 2016;15:391–404.